1980
DOI: 10.1111/j.1651-2227.1980.tb07135.x
|View full text |Cite
|
Sign up to set email alerts
|

The Aarskog Syndrome

Abstract: The Aarskog syndrome is characterized by short stature, peculiar facies, shawl scrotum, cryptorchism, broad, short hands and hyperextensibility of the proximal interphalangeal joints. A boy with typical features of the Aarskog syndrome is presented. The proband's mother, sister and grandmother were short and strongly resembled him. Palmar dermatoglyphics showed the presence of whorls in the interdigital areas of the affected mother and son and the absence of this pattern on the palms of the sister.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Only some disorders with principally postnatal stunting and rather typical facial features will be mentioned: Cockayne syndrome, Hallermann-Streiff syndrome [312], Kenny syndrome [162], Johanson-Blizzard syndrome [51], Aarskog syndrome [108,182] and Williams-Beuren syndrome [123].…”
Section: Syndromes With Mainly Postnatal Growth Retardationmentioning
confidence: 99%
“…Only some disorders with principally postnatal stunting and rather typical facial features will be mentioned: Cockayne syndrome, Hallermann-Streiff syndrome [312], Kenny syndrome [162], Johanson-Blizzard syndrome [51], Aarskog syndrome [108,182] and Williams-Beuren syndrome [123].…”
Section: Syndromes With Mainly Postnatal Growth Retardationmentioning
confidence: 99%
“…Since then several cases have been reported widening the phenotypic spectrum of patients with this condition [Furukawa et al, 1972;Sugarman et al, 1973;Berman et al, 1975;Escobar and Weaver, 1978;F'ryns et al, 1978;Berry et al, 1980;Oberiter et al, 1980;Nielsen, 19881. Recently, Teebi et al [19881 reported on an inbreed Kuwaiti family with a condition closely resembling the Aarskog syndrome (Table I), and suggested autosomal recessive inheritance.…”
Section: Discussionmentioning
confidence: 98%
“…Based on the pattern ofoccurrence in various families, the inheritance of Aarskog syndrome has been interpreted as fitting an X-linked (recessiveisemi-dominant), autosomal dominant (sex-influenced), or autosomal recessive model [Aarskog, 1970[Aarskog, , F'urukawa et al, 1972Sugarman et al, 1973;Oberiter et al, 1980;Grier et al, 1981;Teebi et al, 19881. The main clinical manifestations of patients in these families are similar.…”
Section: Introductionmentioning
confidence: 99%
“…1 Some degree of cognitive impairment is possible, but affected children usually have good social skills. It was first described by Aarskog in 1970 2 and further delineated by Scott in 1971.…”
Section: Introductionmentioning
confidence: 99%
“…Aarskog syndrome is an X-linked recessive condition with affected males demonstrating short stature, limb deformities, facial dysmorphism and genital abnormalities. 1 Some degree of cognitive impairment is possible, but affected children usually have good social skills. It was first described by Aarskog in 1970 2 and further delineated by Scott in 1971.…”
Section: Introductionmentioning
confidence: 99%